(untitled) (Proceedings of the International Conference on Future of Education, 2022)
Open Educational Resources (OER) enables free accessible knowledge to everyone. Higher education institutions in Malaysia have embarked on the OER movement to harness the full potential of open access to educational content in supporting online and distance learning, especially during the current pandemic COVID-19 outbreak. The emergence of OER have successfully made a significant amount of new and existing teaching and learning resources during the current pandemic. For educators and academicians, another significant advantage to OER is the ability to pick and choose of each resource they want to use. However, OER development in Malaysia is still in its infancy which leads for more studies on discoverability, accessibility, and retrieval. This study was conducted to investigate the current landscape of OER initiatives in Malaysian higher education institutions. The study employed a web analysis of 36 top Malaysian universities within the QS Asia University Ranking in 2022. The web analysis (February-July) encompassed a set of checklists on OER standard criteria as: platform hosting, accessibility search interface, a resource guide, alignment subject resources/course, OER repository, copyrights, and licensing, and OER metadata. The findings indicated merely 75% of the universities have initiated OER through their web presence. Only 37% of the universities fulfilled at least 4 criteria from the checklist indicating a need for higher learning to be more proactive in supporting OER development. This may include partnerships with other stakeholders such as libraries, faculties, and ICT centers to fully participate in the OER development following directions toward Sustainable Development Goals (SDGs), on achieving quality education.